Beyond Interactions: INTERACT 2019 IFIP TC 13 Workshops, Paphos, Cyprus, September 2–6, 2019, Revised Selected Papers - (:unkn) unknown (My University, 2026)
Beyond Interactions: INTERACT 2019 IFIP TC 13 Workshops, Paphos, Cyprus, September 2–6, 2019, Revised Selected Papers